Relationship between performance in three of the Centers for Disease Control microbiology proficiency testing programs and the number of actual patient specimens tested by participating laboratories. - Griffin, C W (1986)
The performance of laboratories enrolled in three of the Centers for Disease Control microbiology performance evaluation programs was studied in relation to the number of actual patient specimens tested by the laboratories. Laboratories were grouped according to the number of specimens tested weekly to compare performance among the groups. Results of the study showed that laboratories, as a group, that tested large numbers of specimens performed better than laboratories that tested small numbers. The infrequency of performing certain tests or identifying certain microbial species can be an important factor in laboratory error. One strategy for laboratories that cannot resolve internal problems associated with low testing volumes would be to limit their testing to procedures that are done well.